Moving beyond the therapeutic relationship: a selective review of intimacy in the sexual health encounter in nursing practice. Issue 23 (7th June 2013) - East, Leah; Hutchinson, Marie
Abstract : Aims and objectives: For the purposes of this study, a selective review of the literature was undertaken with the aim of examining nurses' preparedness to engage in intimate interactions within the context of sexual health care. Kirk's (2007) model of interactional intimacy is used as a lens to examine the literature. Background: The provision of sexual health care is often a neglected area of nursing care despite being recognised as a component of holistic nursing practice. Despite theoretical discussion about various forms of intimacy and intimate care, there has been little examination of the interface between intimacy and sexual health care that usefully informs practice. Design: Selective review and synthesis of the literature. Conclusion: The literature of humanistic interpretations of caring that has dominated nursing discourse over the last half‐century has limited progress on defining and developing forms of clinical interaction that are suited to promoting nurses engagement in sexual health care. We propose that Kirk's model has useful utility in preparing nurses to engage more readily with sexual health care as a routine component of their practice. Relevance to clinical practice: Sexual health adversity can often accompany ill health, and therefore, the provision of appropriate care is required to negate detrimental outcomes and promote positive well‐being. Although sexual health care is often not prioritised in practice, nurses are in a prime position to promote sexual health care and well‐being. By conducting sexual health assessments and providing sexual health care routinely, the gap that exists between patients' sexual healthcare needs and the lack of sexual health care provided can be minimised.